PENGARUH PASTA STROBERI (Fragaria ananassa) SEBAGAI BAHAN PENGHILANG STAIN EKSTRINSIK PADA PERMUKAAN GIGI, GIGI TIRUAN, DAN PLAT RESIN AKRILIK - , NUR RAHMAWATI SHOLIHAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Discoloration of the teeth and denture caused aesthetic problems and patient dissatisfaction. Discoloration of teeth, denture teeth, and acrylic resin plate were caused by extrinsic stain which is resulted from daily foods and beverages. Brushing was a method to remove tooth's extrinsic stain, and widely used to clean denture. Strawberries contained malic acid and ellagic acid which could whiten teeth. The aim of this study was to determine the effect of strawberry paste (Fragaria ananassa) as extrinsic stain remover on the surface of teeth, denture teeth and acrylic resin plate. Fifteen teeth, denture teeth, and acrylic resin plate were divided into 3 groups with 5 subjects each, then immersed in black tea solution for 6 days. After the formation of extrinsic stain, subjects were brushed 5 movements per second for 70 seconds using three types of paste which are basic paste, strawberry paste, and Zact ®. Before and after the formation of stain, and after brushing, the image of study subjects were taken and then the average of surface brightness intensity were analyzed with software ImageJ. ANOVA test results showed a significant difference between the paste type to the difference in average surface brightness intensity of research subjects (p <0.05). LSD test results showed a significant difference between the basic paste with strawberry paste and Zact® (p <0.05), and there was no significant difference between strawberry paste with Zact® (p> 0.05). It was concluded that strawberry paste (Fragaria ananassa) influence as extrinsic stain remover on the surface of tooth, denture teeth, and acrylic resin plate. Keywords : teeth, denture teeth, acrylic resin plate, extrinsic stain, Fragaria ananassa, image J